Kepatuhan Penggunaan APD pada Petani : Systematic Review - Anita Camillia; Fitria Saftarina; Wiwi Febriana (Universitas Malahayati Lampung, 2025)
ABSTRACT Farmers are one type of job that requires great physical strength and is exposed to many risks of work accidents and health hazards. One effort to prevent work accidents and occupational diseases is to use Personal Protective Equipment (PPE). However, awareness of the use of PPE among farmers is still low. The use of PPE for farmers certainly requires an assessment related to worker compliance in using PPE when working. To determine the factors of PPE compliance among farmers. The research method used is literature review. Data collection using Google Scholar, Science Direct, Cochrane, and Pubmed internet searches with the keywords